Pengaruh Perundungan (Bullying) Terhadap Prestasi Belajar Siswa dalam Perspektif Pendidikan Agama Islam di Madrasah Tsanawiyah Panca Murni Jatikalen Nganjuk - Adibah Adibah; Eny Fatimatuszuhro Pahlawati; Liya Afifatul Jannah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This study aims to analyze the effect of bullying on students’ learning achievement from the perspective of Islamic Education at Madrasah Tsanawiyah Panca Murni Jatikalen Nganjuk. This research employed a quantitative method with an ex post facto approach. Data were collected through observation, questionnaires, and documentation involving 15 eighth-grade students as respondents. Data analysis was conducted using SPSS, including normality, linearity, t-test, and simple regression tests. The results revealed that the t-value (0.200) < t-table (2.131) and the significance value (0.884) > 0.05, indicating that bullying has no significant effect on students’ learning achievement. However, descriptive findings showed that verbal and relational bullying frequently occurred in the school environment, which negatively affected students’ comfort and learning motivation. From the perspective of Islamic Education, bullying is considered a reprehensible act that contradicts the teachings of the Qur’an and Hadith. Therefore, preventive measures should be strengthened through moral guidance and character education in schools. Keywords: Bullying; Learning Achievement;